A 12-month natural experiment investigating the impacts of replacing a traditional bus service with bus rapid transit on physical activity. (September 2021) - McCormack, Gavin R.; Ghoneim, Dalia; Frehlich, Levi; Blackstaffe, Anita; Turley, Liam; Bracic, Blanka
Abstract: Introduction: Regular physical activity provides numerous health benefits. The neighbourhood built environment is important for supporting physical activity. Despite higher physical activity among public transit users, the effect of introducing Bus Rapid Transit (BRT) services on physical activity remains unclear. We undertook a natural experiment which aimed to estimate changes in transit use and physical activity before and after (12-months) a new BRT service replaced a traditional bus service. Methods: Between August/September 2018 and 2019, a sample of adults (n = 196) (Calgary, Canada) completed two online questionnaires. During the 12-months between questionnaires, new BRT stops replaced existing traditional bus stops. Participants were divided into exposed (n = 80) and comparison (n = 116) groups based on a threshold network distance (800m) between their households and the nearest BRT stop. We undertook propensity score analysis to adjust for baseline differences in sociodemographic characteristics, health behaviours, walkability (Walk Score®), and transit accessibility (Transit Score®) between the exposed and comparison groups and estimated post intervention differences in neighbourhood transportation walking (NWT) and cycling (NTC), moderate-to-vigorous intensity physical activity (MVPA), and transit use and perceive relative change of physical activity during the last 12-months. Results: There were no significant differences in weekly minutes of NWT or NTC between the exposed and comparison groups. Groups were also similar in the accumulation of daily sufficient MVPA and perceived relative change in physical activity after 12-months. Compared with non-users, transit users reported higher (p < .05) NTW minutes per week at baseline and follow-up in the exposed group (156.5 vs. 54.0 and 129.0 vs. 60.5, respectively) and at baseline in the comparison group (103.7 vs. 52.9). Conclusions: Replacing a traditional bus service with a BRT service may have no noticeable immediate impact on physical activity levels. Highlights: Replacing a traditional bus service with BRT did not affect physical activity. Replacing a traditional bus service with BRT increased time spent using transit. Transit users reported higher neighbourhood transport walking minutes than non-users.